Exploring Coherence of the Indonesia Subject Teaching Learning Instructional Process with the National Standard of Curriculum - Rumtini, Rumtini (VOKAL: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2024)
The aims of this study are to explore the Indonesian language Subject -refer to Bahasa Indonesia as instructional practices has coherence or alignment with the national curriculum. This study was designed to apply quantitative descriptive methods in examining class instruction of Indonesian language at junior secondary schools has the level of alignment with the standard national curriculum. This study found majority of teachers described that they had delivered all topics required by the curriculum standard. Interestingly, findings showed that there were only one teacher taught less than 70% of the curriculum standard and also were indicated that only a few teachers  taught less than 100% of the content of the topics set on the  curriculum standard. This number provide evidence the availability of uncovered topics in some areas. This finding should significantly be great concern since the negative effect may be potentially affected on student learning and student performance on the standard national curriculum, further study should be done on this area of the level students’ understanding what teachers’ tauhgt.